Team members' reactions to a gender‐dissimilar leader: Competence monitoring and influence. Issue 10 (27th July 2022) - Li, Jiping; Knippenberg, Daan van; Chattopadhyay, Prithviraj; Wu, Wen
Abstract: Gender bias against female leaders suggests that female leaders are less accepted than male leaders. Moreover, research has suggested that male subordinates are less willing to accept female leaders than their female peers. We propose that their unwillingness to accept a female leader's influence may invite male team members to seek to develop their own influence within the team. Drawing on the theory of social self‐regulation in relational demography, we argue that compared with their female counterparts, male team members are more motivated to increase their influence within the team through competence monitoring (self‐regulated behavior to establish their competence within the team), especially when there is a greater proportion of male peers in the team (i.e., a lower level of gender dissimilarity between themselves and the rest of the team). In turn, we propose that competence monitoring has an increasingly positive relationship with the influence of male members within the team. The findings of our multisource survey of 288 members of 61 research and development teams supported our hypotheses. We discuss the implications of our findings for research on gender and leadership and relational demography.